The Limits of GIS Implementation in Education: A Systematic Review - Veronika Bernhäuserová; Lenka Havelková; Kateřina Hátlová; Martin Hanus (ISPRS International Journal of Geo-Information, 2022)
Despite the extensive discussion on the educational potential of GIS and the changes made in the curricula in many countries, the implementation of GIS in classrooms has still been relatively slow. This is because of variables limiting the process of GIS implementation in lessons. Although research into the limits of GIS implementation has been carried out quite extensively, there is a need for knowledge systematisation in the field. Therefore, the presented systematic review of 34 empirical studies addresses this need and pays attention to the methodological approaches used to research the limits, the identified limits of GIS implementation, their categorisation, and any temporal trends in their occurrence. Altogether, the analysed studies identified 68 limits of GIS implementation in education using mainly quantitative methodology (especially the questionnaire), with utmost attention paid to teachers as participants. These limits then formed complex categorisation that distinguishes elementarily between the limits related to humans and resources. The most frequent and variable category of limits was teachers followed by technology, while both kept their positions in all periods. The systematisation of the research enables the formulation of implications for educational and geoinformatics practice and recommendations for future research.